Optimalkan Promosi Wisata Kabupaten Sijunjung Melalui Pelatihan Pembuatan Website Statis dengan Google Sites untuk Pengelola Objek Wisata Sijunjung - Atma, Yori Adi; Kasmar, Andre Febrian; Wijaya, Taruma Leo; Marni, Enzi; Yofelino, Marcella Putri (Politeknik Piksi Ganesha Indonesia, 2025)
Sijunjung Regency holds significant tourism potential; however, it has yet to be supported by optimal digital promotion. This community engagement project aims to enhance regional tourism promotion through training on static website development using Google Sites for local tourism managers. The training methods include counseling, hands-on tutorials, and guidance in creating and managing informative, accessible websites. The outcome of this project is a static website that integrates information on tourist attractions, facilities, and the unique appeal of Sijunjung Regency, particularly the Geopark Silokek site, accessible at https://www.geoparksilokek.id. This training successfully improved participants' abilities to independently promote local tourism destinations, positively impacting the engagement of managers in digital promotion and providing broader access to tourism information for the public.